2019
DOI: 10.2967/jnumed.119.230318
|View full text |Cite
|
Sign up to set email alerts
|

Total-Body 68Ga-PSMA-11 PET/CT for Bone Metastasis Detection in Prostate Cancer Patients: Potential Impact on Bone Scan Guidelines

Abstract: Our purpose was to determine the relationship between serum prostate-specific antigen (PSA) level categories (,5, 5-10, 10-20, and .20 ng/mL) and the incidence of bone metastases detected by total-body 68 Ga-prostate-specific membrane antigen (PSMA)-11 PET/CT and to assess if expanding the 68 Ga-PSMA-11 PET/CT imaging field to include the vertex and lower extremities (total-body acquisition) affects bone metastasis detection rates and patient management. Methods: This was a retrospective analysis of 388 prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…Ga-PSMA PET(20,23), superior to standard of care imaging including CT or bone scan. The purpose of this study was to evaluate the diagnostic accuracy of 68 Ga-PSMA-11 PET findings in by on November 1, 2020.…”
mentioning
confidence: 99%
“…Ga-PSMA PET(20,23), superior to standard of care imaging including CT or bone scan. The purpose of this study was to evaluate the diagnostic accuracy of 68 Ga-PSMA-11 PET findings in by on November 1, 2020.…”
mentioning
confidence: 99%
“…Monitoring the response of metastatic skeletal disease to treatment and early identification of castration resistance is an ongoing challenge. Measurement of PSA alone is not reliable enough for monitoring disease activity since visceral metastases may develop in men without rising PSA [ 4 ]. The Prostate Cancer Working Group (PCWG) 2 and 3 recommended a combination of bone scintigraphy and CT scans, PSA measurements, and clinical benefit in men with CRPC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate-specific membrane antigen (68Ga-PSMA-11) positron emission tomography/computed tomography (PET/CT) is highly sensitive and specific for detection of skeletal involvement in newly diagnosed prostate cancer patients. It has been shown to be superior to traditional bone scintigraphy (BS) as it allows for detection of lytic type and early marrow-based metastases in addition to osteoblastic-type metastases seen on BS [ 2 , 3 , 4 ]. In a recent study involving 112 prostate cancer patients, 68Ga-PSMA-11 PET/CT revealed bone metastases in 10% of the patients who were deemed to be non-metastatic on BS and in 36% of the patients with indeterminate BS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, 11 C-choline accumulates in liver, kidney, spleen and pancreas, making assessment of the upper abdomen difficult [ 74 ]. More recently, the expression of the prostate-specific membrane antigen (PSMA) was targeted with 68 Ga-labeled PSMA ligands [ 75 , 76 ]. 68 Ga-PSMA-11 PET/CT assists in disease localization at biochemical recurrence (BCR), staging, and to select patients for PSMA-targeted molecular radiotherapy [ 75 ].…”
Section: Nanomedicine and Prostate Cancer Bone Metastasismentioning
confidence: 99%